Intermittent Hypobaric Hypoxia Preconditioning Ameliorates Kidney Damage Compared to Acute Hypoxia - Sadikin, Abdul Halim; Jusman, Sri Widia Azraki; Mulyawan, Wawan; Prijanti, Ani Retno (Bogor Agricultural University, Indonesia, 2025)
Many studies have reported that intermittent hypobaric hypoxia (IHH) can cause oxidative stress and tissue damage in the kidneys, which can lead to impaired kidney function. However, a study using simulated intermittent hypobaric hypoxia was considered to have a protective role for the kidneys. This study aims to determine the effect of IHH on kidney adaptation to oxidative stress and kidney damage. Twenty-five rats were divided into five groups: control, one-time hypoxia (AHH), two-time hypoxia (IHH 1), three-time hypoxia (IHH 2), and four-time hypoxia (IHH 3). The intermittent interval was one week, and at the time of treatment, the rats were placed in a hypoxic chamber. At the end of treatment, the rats were sacrificed, and the kidneys, urine, and blood were collected. The kidney tissues were used for protein assay, ELISA (HIF-1α and VEGF), qPCR (cytoglobin (Cygb) and renin), SOD and GPx activity assay. Blood was used for creatinine and urea assay, and urine was used for KIM-1 ELISA. Formalin-submerged tissues were used for histopathological analysis. The level of HIF-1α and VEGF increased significantly from AHH to IHH 1. Cygb and renin expressions peaked at AHH and decreased at subsequent IHH groups. The Nrf2 level and GPx activity didn’t show any difference, but SOD activity peaked at IHH 1. The creatinine level only peaked at IHH 2; other groups remained the same as the control. Urea levels decreased with more IHH sessions, and KIM-1 didn’t show any difference. Our findings exhibit that hypoxia preconditioning by IHH treatment leads to the kidney’s adaptability to hypoxia and does not cause kidney damage.